A replication of the 5–7day dream-lag effect with comparison of dreams to future events as control for baseline matching - Mark Blagrove (Consciousness and Cognition, 2011)
The dream-lag effect refers to there being, after the frequent incorporation of memory elements from the previous day into dreams (the day-residue), a lower incorporation of memory elements from 2 to 4 days before the dream, but then an increased incorporation of memory elements from 5 to 7 days before the dream. Participants kept a daily diary and a dream diary for 14 days and then rated the level of matching between every dream report and every daily diary record. A significant dream-lag effect for the 5–7 day period, compared to baseline and compared to the 2–4 day period, was found. This may indicate a memory processing function for sleep, which the dream content may reflect. The paper has significant theoretical implications for the time-course of consolidating autobiographical memory.